Melena Revealing an Attenuated Familial Adenomatous Polyposis in an Elderly Patient: A Case Report - N'khaili, Asmaa; Aouroud, Hala; Semlali, Riad; Chakor, Fatimaezzahra; Errami, Adil Ait; Oubaha, Sofia; Semlani, Zouhour; Krati, Khadija (International Journal of Innovative Research in Medical Science, 2022)
We describe a patient who was diagnosed with multiple tubulleuvillous adenomas with focus of high-grade tubular dysplasia all over the colonic mucosa, discovered during a colonoscopy performed during an episode of melena. Genetic testing has identified a germline truncating mutation at the codon (5q22.2) of the adenomatous polyposis (APC) gene. This mutation is localized in the alternately spliced region of exon 12, a region which is associated with an attenuated familial adenomatous polyposis (PAFA) phenotype. Our patient had no extracolic manifestations of PAFA and none of her relatives had a history of rectocolic polyposis. Treatment consisted of colectomy with ileorectal anastomosis. PAFA is an ill-defined condition of unknown prevalence and penetrance, requiring individual treatment and lifelong monitoring. It is essential to identify these patients with a view to setting up appropriate endoscopic surveillance at an early age in family members carrying this mutation, due to the marked intra-family phenotypic variance.